Pengaruh Metode Tanya Jawab Terhadap Prestasi Belajar Siswa Mata Pelajaran Akidah Akhlaq Kelas IV Di Madrasah Ibtidaiyah Muhammadiyah 06 Brondong Lamongan - Maftuhah Maftuhah; M.Chotibuddin; Aaisah Arsae (STIT Muhammadiyah Paciran Lamongan, 2021)
This study aims to determine the application of the question and answer method and how it affects student achievement in the fourth grade Akidah Akhlaq subjects at MI Muhammadiyah 06 Brondong Lamongan. This research uses descriptive quantitative research. The subjects in this study were 50 students. By using the instrument in the research is a questionnaire, observation and documentation. The results showed that the value of the coefficient of r arithmetic on r table with the number of N = 50 for a significant level of 0.279 or 5%, then r count = 9.440 > r table = 0.279 and for a significant level of 0.361 or 1% then r count = 9.440 > r table = 0.361 thus r count is greater than r table. Then it can be said that Ho is rejected and Ha is accepted.